Leitura nas interfaces gráficas de computador: compreendendo a gramática da interface - Ana Elisa Costa Novais (2009)
Reading the computer graphical Interface which uses an interdisciplinary net of studies about text, design, reading and cognition in order to depict both constructions of meaning and textualization strategies is the object of this study. We have understood interface as a text, a point of contact between the author/designer and the reader/userbased on the hypotheses that both, the understanding of the relatively stable marks of those texts and the grammar that underlies that kind of genre, facilitate the transit within the interface and help to understand the dynamics that rules such semiotic system. We have chosen four students having little experience in both computing and readingpractices on computers as the object of this study. Reading tests from which the students would develop tasks on Power Point and Paint based on printed patterns were made. Those tests generated verbal protocols which were analyzed according to both the Restructured Model of reading (COSCARELLI, 1999) and the Conceptual Blending theory (FAUCONNIER, TURNER, 2002). With the restructured model in hands, we searched for theoretical support in order to deal with the domains of reading which had been activated when the tasks on computer were in progress. By articulating concepts on usability and readability, we have cast some features of the interfaces (textuality) that favor its own textualization unity recognition (access to the icons), syntacticdomain (sequence of browsing) and semantic domain (complementary reference from analogies, metaphors, generalizations, judgments, among others). Blending theory gave us the chance to know the high level cognitive operations aroused by reference processes of mental spaces activating, mapping, projections, complementation andcompressions of vital relationship (Category, Property, Analogy, Identity, Similarity, and Reference). It was possible to deconstruct some typical features of the interfaces and their variation among the programs, like differences on treating distinct objects (text, picture, textbox, and so on) and notice the difficulty faced by the users to understand them, make analogies among those objects, and understand them not only asComplex Categories of Property, but as distinct ones as well. Reading Interfaces, we conclude, depend not only on recognizing icons and other graphic elements, but also on the integration of several formal elements that make up its complex and coherent organizational dynamics. In order to read the interfaces and use the computer, it is necessary the construction of a knowledge that evolves concepts completely differentfrom both literate practices and texts, and supports. The skill to cast and integrate those concepts, by making use of standard conceptual structures and more stable and coherent interfaces as much as to an ampler idea of computing, facilitates operations on computer. In this sense, the more the user disposes and articulates knowledge, the lesspreconceptions of the common sense he/she raises from the blending, more confident to create and test hypotheses he/she feels to make the required connections in order to accomplish his/her tasks.